FAKTOR PENENTU KEPUASAN MASYARAKAT PADA PELAYANAN KARTU TANDA PENDUDUK ELEKTRONIK (E-KTP) DI KECAMATAN PRACIMANTORO, KABUPATEN WONOGIRI - Yosephine Angelina; Gita Safitri (Jurnal Bisnis Terapan, 2018)
This research is used to know and analyze any determinant factors that affect Quality of Identity Card (E-KTP) Service to Satisfaction of Society in Pracimantoro Sub-district, Wonogiri Regency. The method used in this research is the method of observation and questionnaire by using Likert scale. Sampling method used using convenience sampling method as many as 100 samples. The method of analysis used is the test of validity, reliability test, classical assumption test, multiple linear regression test. The result of multiple linear regression test shows that the service quality consisting of Tangibles (X1), Assurance (X2) and Empathy (X3) partially or individually has a significant influence on the satisfaction of society. Where the regression equation Y = 1.853 + 0.251X1 + 0.106X2 + 0.162X3 + 0.207X4 + 0.196X5. The result of t test shows that the quality of service consisting of Tangibles (X1), Assurance (X2) and Empathy (X3) has significant effect on the satisfaction of the community is shown by significant of each variable <0,05. In the F test results obtained value obtained Fcount value of 22.732 with a significance level of 0.000 <0.05 this means that the variables together have a significant influence on community satisfaction.